2020
DOI: 10.1177/0020764019899978
|View full text |Cite
|
Sign up to set email alerts
|

‘I wanted my child dead’ – Physical, social, cognitive, emotional and spiritual life stories of Turkish parents who give care to their children with schizophrenia: A qualitative analysis based on empowerment approach

Abstract: Background: Schizophrenia deeply affects both the lives of patients and their families. The fact that schizophrenic patients in Turkey generally maintain their lives with their families may lead to serious problems for families and parents. Aims: The main purposes of this research are to determine the physical, social, cognitive, emotional and spiritual lives of parents of children with schizophrenia with the main concepts of the empowerment approach. Method: The research was carried out with the qualitative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…The study found that families have various resources, including the majority being well educated (38.5%), as private employees (37.8%), 65% are still productive age (20-55 years), use non private insurance (95.6%) and rely on main family members as caregivers, namely siblings (39.3%) followed by Mother and Father. This is reinforced by the theory that to treat schizophrenic patients, the family will activate existing resources and create new resources [7], [32]. The main family members' involvement as caregivers shows that one of the family resources is the family structure.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The study found that families have various resources, including the majority being well educated (38.5%), as private employees (37.8%), 65% are still productive age (20-55 years), use non private insurance (95.6%) and rely on main family members as caregivers, namely siblings (39.3%) followed by Mother and Father. This is reinforced by the theory that to treat schizophrenic patients, the family will activate existing resources and create new resources [7], [32]. The main family members' involvement as caregivers shows that one of the family resources is the family structure.…”
Section: Discussionmentioning
confidence: 99%
“…The family's ability to provide care for schizophrenic patients was found to be low. Schizophrenic families at Menur Regional Psychiatric Hospital can care for patients at a moderate level (49.6%) [6], while the family's ability to treat schizophrenia in the Naras Public Health Center working area in Padang is also poor at 46.1% [7]. The majority Int J Public Health Sci ISSN: 2252-8806  Factors related to family's ability to care for schizophrenic patients (Dwi Indah Iswanti) 765 of families experience fatigue and suffering [8].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations